2016
DOI: 10.1371/journal.pgen.1006325
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Recovery of Sensory Cilia in C. elegans IFT Mutants upon Aging

Abstract: The majority of cilia are formed and maintained by the highly conserved process of intraflagellar transport (IFT). Mutations in IFT genes lead to ciliary structural defects and systemic disorders termed ciliopathies. Here we show that the severely truncated sensory cilia of hypomorphic IFT mutants in C. elegans transiently elongate during a discrete period of adult aging leading to markedly improved sensory behaviors. Age-dependent restoration of cilia morphology occurs in structurally diverse cilia types and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 98 publications
1
21
1
Order By: Relevance
“…At days 4 and 8 of adulthood for MKS-6 ("MKS module" TZ protein), and day 4 for NPHP-4 ("NPHP module" TZ protein), ectopic TZ protein localisation is reduced compared to 1-day-old adults (Figs 5A and B, and EV5A and B). While perhaps surprising, our findings are consistent with those of Cornils and colleagues [76], who reported an improvement in cilia morphology (TZ was not looked at) for some hypomorphic IFT mutants during ageing, a process requiring IFT. However, we also discovered a significant, age-dependent difference in the ability of ts-che-3 mutant animals to restore their ciliary structures when shifted from restrictive to permissive temperature (Figs 5A and B, and EV5A and B).…”
Section: Cilia Repair Potential Decreases In Older Animalssupporting
confidence: 92%
“…At days 4 and 8 of adulthood for MKS-6 ("MKS module" TZ protein), and day 4 for NPHP-4 ("NPHP module" TZ protein), ectopic TZ protein localisation is reduced compared to 1-day-old adults (Figs 5A and B, and EV5A and B). While perhaps surprising, our findings are consistent with those of Cornils and colleagues [76], who reported an improvement in cilia morphology (TZ was not looked at) for some hypomorphic IFT mutants during ageing, a process requiring IFT. However, we also discovered a significant, age-dependent difference in the ability of ts-che-3 mutant animals to restore their ciliary structures when shifted from restrictive to permissive temperature (Figs 5A and B, and EV5A and B).…”
Section: Cilia Repair Potential Decreases In Older Animalssupporting
confidence: 92%
“…Primary cilia and aging have been investigated by several studies. Cornils et al 40 reported the increased variability in ASI cilia length as animal aged. Recently, it was reported that primary cilia length are frequently changed in agingā€related and neurodegenerative disorders 41 .…”
Section: Discussionmentioning
confidence: 99%
“…While degenerative ciliary phenotypes may become progressively worse with time, a developmental phenotype may improve with time in certain mutant backgrounds. A recent publication may already have showed evidence of this, describing structural and functional time-dependent recovery of sensory cilia from young adulthood to middle age in C. elegans hypomorphic mutants previously known for axonemal structural defects (Barr, 2016;Cornils et al, 2016). Similarly, Drosophila mutants that lack TZlocalizing MKS proteins and show axonemal structural defects in larval development recover in adulthood (Pratt et al, 2016).…”
Section: Wild-type Cem and Il2 Tzs Have Incomplete Dmts And Smts Withmentioning
confidence: 99%